An International Perspective on the Nexus of Physical Activity Research and Policy. (January 2016) - Pratt, Michael; Salvo, Deborah; Cavill, Nick; Giles-Corti, Billie; McCue, Peter; Reis, Rodrigo S.; Jáuregui, Alejandra; Foster, Charlie
The traditional view of translating research to policy is reframed as a complex multidirectional interaction based on international case studies presented at the 2015 Active Living Research conference. The United Kingdom developed a process for reviewing and synthesizing evidence to inform policy, but policy makers were often ahead of the guidance. In Australia, translation of research to policy has been facilitated by brokering the relationship between researchers and policy makers. The best example of dissemination of the evidence for physical activity promotion into a national program comes from Brazil, but implementation has been markedly influenced by community and political factors. In Mexico, "physical activity policy" is being implemented at scale but without much research and with leadership from sectors other than public health. A more flexible understanding of the complex interplay between research and policy will increase the probability that the best available evidence will influence policy and that policy with the potential to increase physical activity will be evaluated.